Macroscopic compressive strength study of historical grey bricks based on microscopic scale - Yue, Jianwei; Lei, Yang; Zhu, Xiang; Xu, Shaopeng; Yue, Mengen (Construction & building materials, 2024)
Determining the macroscopic compressive strength of original grey bricks in historical structures has become a crucial topic due to rules and legislation about the preservation of cultural artifacts and illnesses like weathering. This work aims to provide a microscale approach for estimating the macroscopic compressive strength of historical grey bricks. This method, based on nanoindentation and mercury intrusion porosimetry, divides the historical grey bricks into two representative volume elements (RVEs) at the observation scale with continuous transition: A microscale Mori-Tanaka equivalent RVE encompassing microstructural features, which nanoindentation, X-ray diffraction, scanning electron microscopy, mercury intrusion porosimetry, and other tests obtain the features. A mesoscale RVE representing the two-phase model of a "porous inclusions-equivalent matrix." Then, the prediction of macroscopic compressive strength of the historical grey brick is realized by the simulation of the uniaxial compression of the mesoscale RVE. For the three types of historical grey bricks (A, B, and C), the errors in the predictions obtained by the multiscale micromechanical models, in comparison to the macroscopic experimental results, are 13.67%, 10.34%, and 5.22%, respectively. Compared to conventional mechanical experiments and non-destructive methods, this approach exhibits comprehensive information acquisition, minimal influence from human factors, and minimal subject disturbance. It is well-suited for obtaining performance parameters of intrinsic materials in historical buildings, grottoes, nuclear power plants, etc. •This study proposes a multiscale method for determining the macroscopic compressive strength of historical grey bricks.•Two representative volume elements at the micro- and meso-scales are established using the continuum micromechanics approach.•Parameters at the microscale are obtained by nanoindentation, X-ray diffraction, and energy dispersive spectroscopy methods.•A two-phase model consisting of the porous phase and the equivalent matrix is constructed at the mesoscale.•This approach is well-suited for obtaining the performance parameters of intrinsic materials.